Pengaruh Waktu Penyimpanan Larutan Oral Nutraceutical Ekstrak Bunga Delima Merah (Punica Granatum L.) Terhadap Perubahan Hambatan Pertumbuhan Pseudomonas Aeruginosa (In Vitro) - Liyundzira, Liyundzira; , drg. Mahmud Kholifa, MDSc (2017)
Pseudomonas aeruginosa is a normal flora of the oral cavity, although as a normal flora the oral cavity of this bacteria can turn into a pathogen because of the supporting factors such as poor oral hygiene. Pseudomonas aeruginosa can be prevented by the use of bioactive compounds that have antibacterial content. Red pomegranate flowers (Punica granatum L.) are known to contain antibacterials such as flavonoids, phenols and proanthocyanidins. Factors that influence changes in bacterial growth resistance to storage time are temperature, light and humidity. The aim of this research is to know the effect of the time of storage of oral solution of nutraceutical red pomegranate extract (Punica Granatum L.) to the change of growth resistance of Pseudomonas aeruginosa (in vitro). The type of research used in this research is True Experimental Postest Only Control Group Design using 5% concentration. Red pomegranate flowers are extracted by maceration method and the preparation of oral nutraceutical solution is made. Oral nutraceutical solution of red pomegranate extract will be stored from before storage, stored 7 days, stored 14 days, saved 21 days, and stored 28 days by taking into account the environmental factors that is, light, temperature and humidity. The results showed that the effect of the time of storage of oral solution of nutraceutical extract of red pomegranate flowers to Pseudomonas aeruginosa growth barrier. The result of One Way Anova test showed that p = 0,001 (p <0,05), then result of Post Hoc LSD test showed significant value p <0,05 after 21 days storage, so it can be concluded that the oral solution time of oral nutraceutical red pomegranate extract (Punica Granatum L.) had no significant effect on changes in Pseudomonas aeruginosa growth resistance up to 21 days' storage time.